EFEKTIVITAS PENGADAAN BARANG DAN JASA BERBASIS ELEKTRONIK (E- PROCUREMENT) DI KELURAHAN CAKUNG BARAT - Iwan Irwansyah, Iwan Irwansyah; Zahran, Wahidin Septa; Lase, Rosmillah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Procurement of electronic-based goods and services e-procurement is the process of transferring ownership of goods and services by buyers to sellers that occurs through cooperation. West Cakung has been implementing this e-procurement since 2017. This research aims to find out how effective the procurement of e-procurement electronic-based goods and services in West Cakung Village is and also to find out supporting factors and obstacles and solutions in the procurement of e-procurement electronic-based goods and services in West Cakung Village. The type of research used is a type of qualitative descriptive research and is supported by secondary data. The theory used in this study is the theory of effectiveness according to Duncan, namely the effectiveness of achieving goals, integration, and adaptation. And use indicators of policy implementation according to George Edwards III Theory, communication, resources, dispositions, and bureaucratic structures. The data collection techniques used are observation, interview, literature, and documentation. The results illustrate that the exploration of e-procurement in the procurement of government goods and services in West Cakung Village has been effective.